2015
DOI: 10.1093/neuonc/nov015
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implementation of integrated whole-genome copy number and mutation profiling for glioblastoma

Abstract: Combined use of multiplexed copy number and mutation detection from FFPE samples in the clinical setting can efficiently replace singleton tests for clinical diagnosis and prognosis in most settings. Our results support incorporation of these assays into clinical trials as integral biomarkers and their potential to impact interpretation of results. Limited tumor suppressor variant capture by targeted genotyping highlights the need for whole-gene sequencing in glioblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…Contrary to adult oligodendrogliomas, the one anaplastic oligodendroglioma in our cohort did not harbor IDH1/2 mutations or 1p/19q co-deletion [19,22,26]. We detected KRAS G12V, EGFR R222C, and TERT promoter 2124C>T mutations, a Abbreviations: DIPG, diffuse intrinsic pontine glioma; EGFR, epidermal growth factor receptor; NOS, not otherwise specified; pHGG, pediatric high-grade glioma.…”
Section: Genomic Landscape Of Phggsmentioning
confidence: 51%
“…Contrary to adult oligodendrogliomas, the one anaplastic oligodendroglioma in our cohort did not harbor IDH1/2 mutations or 1p/19q co-deletion [19,22,26]. We detected KRAS G12V, EGFR R222C, and TERT promoter 2124C>T mutations, a Abbreviations: DIPG, diffuse intrinsic pontine glioma; EGFR, epidermal growth factor receptor; NOS, not otherwise specified; pHGG, pediatric high-grade glioma.…”
Section: Genomic Landscape Of Phggsmentioning
confidence: 51%
“…Indeed, the unique biology, mutational landscape and predominant signaling pathways in HNC may explain the discrepancy in PD-L1 expression. It has been recently reported that PTEN loss-of-function mutations are frequent in glioblastoma (31.9% of specimens, TCGA data) (42). Furthermore, PD-L1 was upregulated after PTEN loss/PI3K activation in glioblastoma lines, suggesting that gliomas may rely more on this signaling pathway (17).…”
Section: Discussionmentioning
confidence: 99%
“…IDH1/2 mutations were determined using immunohistochemistry, 22 mass spectrometry-based mutation genotyping (OncoMap), 22,23 or multiplex exome sequencing (OncoPanel) 8,24 depending on which genotyping technologies were available at the time of diagnosis. For this retrospective study, only gliomas with absence of IDH1/2 mutations as determined by full sequencing assay with OncoPanel, were included in our analyses as IDH-WT gliomas.…”
Section: Tissue Diagnosis and Genotypingmentioning
confidence: 99%